Comparison of the Applicability of Mass Spectrometer Ion Sources Using a Polarity—Molecular Weight Scattergram with a 600-Sample In-House Chemical Library. Issue 2 (April 2015) - Sugimura, Natsuhiko; Furuya, Asami; Yatsu, Takahiro; Shibue, Toshimichi
To provide a practical guideline for the selection of a mass spectrometer ion source, we compared the applicability of three types of ion source: direct analysis in real time (DART), electrospray ionization (ESI) and fast atom bombardment (FAB), using an in-house high-resolution mass spectrometry sample library consisting of approximately 600 compounds. The great majority of the compounds (92%), whose molecular weights (MWs) were broadly distributed between 150 and 1000, were detected using all the ion sources. Nevertheless, some compounds were not detected using specific ion sources. The use of FAB resulted in the highest sample detection rate (>98%), whereas the detection rates obtained using DART and ESI were slightly lower (>96%). A scattergram constructed using MW and topological polar surface area (tPSA) as a substitute for molecular polarity showed that the performance of ESI was weak in the low-MW (<400), low-polarity (tPSA < 60) area, whereas the performance of DART was weak in the high-MW (>800) area. These results might provide guidelines for the selection of ion sources for inexperienced mass spectrometry users.